2019
DOI: 10.1111/jcmm.14224
|View full text |Cite
|
Sign up to set email alerts
|

PECAM‐1 modulates liver damage induced by synergistic effects of TNF‐α and irradiation

Abstract: The mechanisms of radiation‐induced liver damage are poorly understood. We investigated if tumour necrosis factor ( TNF )‐α acts synergistically with irradiation, and how its activity is influenced by platelet endothelial cell adhesion molecule‐1 (PECAM‐1). We studied murine models of selective single‐dose (25 Gy) liver irradiation with and without TNF ‐α application (2 μg/mouse; i.p.). In serum of wild‐type (wt)‐mice, irradiation induced a mild increase in hepatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
13
0
Order By: Relevance
“…It has been previously reported that the decreased expression of ICAM-1 (Liu et al 2017) and the unstable expression of PECAM-1 can increase the permeability of the endothelium as they act as key molecules for this phenotype (Liu et al 2011, Woodfin et al 2007. This observation was corroborated by a recent study that has revealed that PECAM-1 may have anti-inflammatory and proinflammatory roles in the cells (Malik et al 2019). In addition to this process, the increase in vascular permeability is dependent on the binding of monocytes to endothelial cells, causing activation of the ICAM-1-mediated Src Kinase signaling protein (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 62%
“…It has been previously reported that the decreased expression of ICAM-1 (Liu et al 2017) and the unstable expression of PECAM-1 can increase the permeability of the endothelium as they act as key molecules for this phenotype (Liu et al 2011, Woodfin et al 2007. This observation was corroborated by a recent study that has revealed that PECAM-1 may have anti-inflammatory and proinflammatory roles in the cells (Malik et al 2019). In addition to this process, the increase in vascular permeability is dependent on the binding of monocytes to endothelial cells, causing activation of the ICAM-1-mediated Src Kinase signaling protein (Liu et al 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, breeding PECAM1 flox/flox mice with mice that express Cre recombinase in CD4 + T cells (Kim et al, ) can help to verify their postulated role in resistance to bacterial infection (Ross et al, ). Finally, PECAM1 flox/flox and tissue‐specific Cre recombinase‐expressing mice can be used to identify the specific PECAM‐1‐expressing cells that control inflammatory diseases of the liver (Goel et al, ; G. Malik et al, ; I. A. Malik et al, ) and lung (Schenkel et al, ), and that interfere with tumor clearance (Ma et al, ; D. K. Newman et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, PECAM‐1 was found to enhance hemostasis (Lishnevsky et al, ; Mahooti et al, ) and inhibit thrombosis (Falati et al, ; Kellermair et al, ). PECAM‐1 was also found to play protective roles in autoimmunity (Cheung et al, ; Clement et al, ; Graesser et al, ), inflammatory diseases of the liver (Goel et al, ; G. Malik, Wilting, Hess, Ramadori, & Malik, ; I. A. Malik et al, ) and lung (Schenkel, Chew, Chlipala, Harbord, & Muller, ), and in sepsis (Carrithers et al, ; Maas et al, ; Privratsky, Tilkens, Newman, & Newman, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A single injection of TAA evokes reversible damage of the liver parenchyma in rodents [23]. We have previously shown that Pecam-1-regulated pathways play an important role during tissue damage, and we could further demonstrate liver-protective effects of PECAM-1 by using Pecam-1-deficient mice in acute inflammation models [24,25,26]. Thereby, PECAM-1 appeared to be an interesting candidate for inflammation-triggered liver cancer.…”
Section: Introductionmentioning
confidence: 99%